11C-Labeling of acyclic retinoid peretinoin by rapid C-[11C]methylation to disclose novel brain permeability and central nervous system activities hidden in antitumor agent. (1st April 2023) - Suzuki, Keiichi; Koyama, Hiroko; Nakamura, Narumasa; Kimura, Yasuyuki; Ogata, Aya; Ikenuma, Hiroshi; Ishii, Hideki; Zhang, Ming-Rong; Kawamura, Kazunori; Minamimoto, Takafumi; Nagai, Yuji; Katsuki, Hiroshi; et al.
Graphical abstract: Highlights: Synthesis of 11 C-labeled acyclic retinoid [ 11 C]peretinoin and its esters without double-bond isomerization by Pd(0)-mediated rapid C -[ 11 C]methylation. Novel high brain permeability of 11 C-labeled [ 11 C]peretinoin whereas the corresponding 11 C-labeled ester showed a unique time-activity curve like a prodrug. Disclosing the CNS activities from anti-tumor peretinoin such as differentiation-inducing activity for stem cells to neuronal ones. Abstract: Recently, retinoid actions on the central nervous system (CNS) have attracted considerable attention from the perspectives of brain disease diagnosis and drug development. Firstly, we successfully synthesized [ 11 C]peretinoin esters (methyl, ethyl, and benzyl) using a Pd(0)-mediated rapid C -[ 11 C]methylation of the corresponding stannyl precursors without geometrical isomerization in 82%, 66%, and 57% radiochemical yields (RCYs). Subsequent hydrolysis of the 11 C-labeled ester produced [ 11 C]peretinoin in 13 ± 8% RCY ( n  = 3). After pharmaceutical formulation, the resulting [ 11 C]benzyl ester and [ 11 C]peretinoin had high radiochemical purity (>99% each) and molar activities of 144 and 118 ± 49 GBq μmol −1 at total synthesis times of 31 min and 40 ± 3 min, respectively. Rat brain PET imaging for the [ 11 C]ester revealed a unique time-radioactivity curve, suggesting the participation of the acid [ 11 C]peretinoin for the brain permeability. However, the curve of the [ 11 C]peretinoin rose steadily after a shorter time lag to reach 1.4 standardized uptake value (SUV) at 60 min. These various phenomena between the ester and acid became more pronounced in the monkey brain (SUV of > 3.0 at 90 min). With the opportunity to identify high brain uptake of [ 11 C]peretinoin, we discovered CNS activities of a drug candidate called peretinoin, such as the induction of a stem-cell to neuronal cell differentiation and the suppression of neuronal damages.